2021
DOI: 10.3390/agronomy11122456
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Accumulation and Phytoremediation Potential of Four Crop Plants Cultivated on Pure Sewage Sludge

Abstract: Phytoremediation is a viable strategy to remove trace metal contaminants from sewage sludge but still is poorly investigated. The aim of this study was to quantify the trace metal removal of B. napus, B. juncea, H. annuus, Z. mays grown on pure sewage sludge. Each species was grown on six different sewage sludge for 8 weeks and sludge were analysed for trace metal content and physico-chemical characteristics. Our results confirmed that all the tested sludge supported plant growth. The tested sludge showed a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Compost and MF application may cause physiological changes in plants as well as changes in soil physical properties and plant nutrients regime, all of which influence As uptake in crops. The BAF indicates the As enrichment in plant biomass, and this ratio is also used to compare the accumulation efficiency of different metals in the soil–plant system 47,48 . The BAF results indicate a change in As mobility from soil to leaves due to the application of either MF or compost, whereas TF values following both MF and compost application show that As showed a significant decrease in translocation from roots to leaves with respect to the unfertilized control.…”
Section: Discussionmentioning
confidence: 99%
“…Compost and MF application may cause physiological changes in plants as well as changes in soil physical properties and plant nutrients regime, all of which influence As uptake in crops. The BAF indicates the As enrichment in plant biomass, and this ratio is also used to compare the accumulation efficiency of different metals in the soil–plant system 47,48 . The BAF results indicate a change in As mobility from soil to leaves due to the application of either MF or compost, whereas TF values following both MF and compost application show that As showed a significant decrease in translocation from roots to leaves with respect to the unfertilized control.…”
Section: Discussionmentioning
confidence: 99%
“…Each sludge was characterized by the marked presence of one or more contaminants among As, Ni, Se and Zn investigated in the present study. P1 is a small WWTP of 25,000 population equivalent (PE) and is characterized by the presence of Ni and As in SS (928 and 35 mg/kg DW), P2 is a medium-large WWTP of 450,000 PE and produces sludge enriched in Se (18 mg/kg DW), P3 is a large WWTP of 500,000 PE and produces Zn-enriched SS (1882 mg/kg DW) (Salinitro et al 2021). Each WWTP was sampled twice, two months apart, to take into consideration sludge variability.…”
Section: Sewage Sludge Collectionmentioning
confidence: 99%
“…The phytoextraction potential of these hyperaccumulator species was already studied on polluted soils, natural ultramafic soils and mine tailings (Bani et al 2015b;Barrutia et al 2011;Chen et al 2018). To date, very few studies focused on the application of phytoextraction to achieve trace elements removal from pure sewage sludge (Nissim et al 2018;Salinitro et al 2021), and even less used hyperaccumulator species (Qiu et al 2014). In particular, Salinitro et al (2021) demonstrated that phytoextraction is technically applicable to pure SS by growing commonly cultivated crop species such as Brassica juncea L., B. napus L., Helianthus annuus L. and Zea mays L. on 6 different SSs, obtaining in all cases plant biomasses comparable or superior to those of control soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these physical and chemical approaches have exposed their limitations due to the requirement of continuous supervision, high cost, and other operational problems. Thus, developing a new method or approach to reduce metal concentration within the limits for its use as fertilizer or agriculture inputs is nowadays considered a challenging goal [24]. To this extent, phytoremediation may represent a viable strategy to clean up industrial sludge and this approach is found to be more environmentally and economically sustainable [25].…”
Section: Phytoremediation Of Industry Sludgementioning
confidence: 99%